Nur77 prevents excessive osteoclastogenesis by inducing ubiquitin ligase Cbl-b to mediate NFATc1 self-limitation - Li, Xiaoxiao (eLife, 2015)
Osteoclasts are bone-resorbing cells essential for skeletal remodeling. However, over-active osteoclasts can cause bone-degenerative disorders. Therefore, the level of NFATc1, the master transcription factor of osteoclast, must be tightly controlled. Although the activation and amplification of NFATc1 have been extensively studied, how NFATc1 signaling is eventually resolved is unclear. Here, we uncover a novel and critical role of the orphan nuclear receptor Nur77 in mediating an NFATc1 self-limiting regulatory loop to prevent excessive osteoclastogenesis. Nur77 deletion leads to low bone mass owing to augmented osteoclast differentiation and bone resorption. Mechanistically, NFATc1 induces Nur77 expression at late stage of osteoclast differentiation; in turn, Nur77 transcriptionally up-regulates E3 ubiquitin ligase Cbl-b, which triggers NFATc1 protein degradation. These findings not only identify Nur77 as a key player in osteoprotection and a new therapeutic target for bone diseases, but also elucidate a previously unrecognized NFATc1→Nur77→Cblb—•NFATc1 feedback mechanism that confers NFATc1 signaling autoresolution. DOI: http://dx.doi.org/10.7554/eLife.07217.001